Supporting underserved patients with their medicines: a study protocol for a patient/professional coproduced education intervention for community pharmacy staff to improve the provision and delivery of Medicine Use Reviews (MURs) - Latif, Asam; Pollock, Kristian; Anderson, Claire; Waring, Justin; Solomon, Josie; Chen, Li-Chia; Anderson, Emma; Gulzar, Sulma; Abbasi, Nasa; Wharrad, Heather (BMJ Publishing Group, 2016)
Introduction